The effect and mechanisms of music therapy on the autonomic nervous system and brain networks of patients of minimal conscious states: a randomized controlled trial - Xiao, Xiang; Chen, Wenyi; Zhang, Xiaoying (Frontiers in Neuroscience, 2023)
In the present study, 20 patients diagnosed with minimally consciousness state (MCS) were selected, and a total of 15 patients completed the experiment. All patients were randomly assigned to three groups: an intervention group (music therapy group, n=5), a control group (familial auditory group, n=5), and a standard care group (no sound stimulation group, n=5). All three groups received 30 minutes of therapy five times a week for a total of 4 weeks (20 times per group, 60 times in total). Autonomic nervous system (ANS) measurements, Glasgow Coma Scale (GCS), and functional magnetic resonance - diffusion tensor imaging (fMRI-DTI) were used to measure the peripheral nervous system indicators and brain networks, and to evaluate patients' behavior levels. The results reveal that PNN50 (p=0.0004**), TP (p=0.0003**), VLF (p=0.0428**), and LF/HF (p=0.0001**) in the music group were significantly improved compared with the other two groups. Such findings suggest that the autonomic nervous system (ANS) of patients with minimally conscious state (MCS) exhibits higher activity levels during music exposure compared to those exposed to family conversation or no auditory stimulation. In fMRI-DTI detection, due to the relative activity of ANS in the music group, the ascending reticular activation system (ARAS) in the brain network also exhibited significant nerve fiber bundle reconstruction, superior temporal gyrus (STG), transverse temporal gyrus (TTG), inferior temporal gyrus (ITG), limbic system, corpus callosum, subcorticospinal trace, thalamus and brainstem regions. In the music group, the reconstructed network topology was directed rostrally to the diencephalon's dorsal nucleus, with the brainstem's medial region serving as the hub. This network was found to be linked with the caudal corticospinal tract and the ascending lateral branch of the sensory nerve within the medulla. As such, music therapy, as an emerging treatment for DOC, appears to be integral to the awakening of the peripheral nervous system-central nervous system based on the hypothalamic-brainstem-autonomic nervous system (HBA) axis, and is worthy of clinical promotion. The research was supported by the Beijing Science and Technology Project Foundation of China, No. Z181100001718066, and the National Key R&D Program of China No. 2022YFC3600300, No. 2022YFC3600305.